Optimasi Antarmuka Website Sistem Pendataan Publikasi Pada Program Studi Informatika Udayana - I Kadek Revan Aditya Prawira; I Wayan Santiyasa; I Wayan Supriana (Jurnal Pengabdian Informatika, 2026)
Publications are activities that disseminate research through scientific journals in the form of articles. Publication data management in the Informatics Study Program at Udayana University is still conducted using Google Forms. This method has limitations, such as restricted features, suboptimal design, and lack of efficient data history access. The proposed solution is a web-based system that improves publication data management, from data collection to publication monitoring. It is expected to overcome Google Form’s limitations and increase data management efficiency. The system involves two user types students and admins. Students can log in, view information, upload files, check review results, make revisions, and update file status. Admins can log in to add, edit, delete information, and record the review results of student files.